Pengaruh Lingkungan dan Motivasi Kerja bagi Karyawan Koperasi BMT Mandiri Sejahtera Jawa Timur Unit Dukun Gresik - M. Syaiful Arif; Ahmad Afan Zaini; Siswadi (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2020)
In a company, leaders must have the ability to control their employees. Leaders must provide motivation to employees, motivation can be in the form of attention and appreciation in accordance with what the employees have given, so employees feel the need for fairness and can also encourage high morale to work. Likewise with the work environment, if the working conditions are clean, comfortable and safe. In this way, employees become motivated to work even better, and ultimately employee performance is achieved. This study uses primary data and secondary data. The primary data here is obtained from indirect interviews obtained from the results of questionnaires filled out by employees, secondary data is obtained from the report data of the sharia financial institution of the BMT Mandiri Prosperous Cooperative East Java. The analytical tool used in this research is multiple linear regression, the results of the analysis are then analyzed by using the F test and statistical t test. (F-test) at the 95% confidence level. And from the results of the third hypothesis analysis shows that the magnitude of the regression coefficient for the work environment variable is 0.191 and the motivation variable is 0.286, so it can be concluded that motivation is the dominant factor that has an influence in improving employee performance at the BMT Mandiri Sejahtera Cooperative, East Java, Dukun Unit.